Systematic Literature Rreview: Pengaruh Polifenol Delima (punicagranatum l.) terhadap Kadar Interleukin-6 pada Penyakit yang Melibatkan Patofisiologi Inflamasi - Ariya Indra Krisna; Ike Widyaningrum; Doti Wahyuningsih (Jurnal Kedokteran Komunitas, 2021)
Introduction: Interleukin-6 (IL-6) is one of the citokynes released by macrophage and patologic cells it has a main role in mediating inflammation. Pomegranate (Punica granatum l.) contain polyphenol such as punicalagin, ellagic acid, urolithin, gallic acid, and delphinidin which has high anti-inflammation activity. Research done this far is the ability of pomegranate to decrease IL-6 level in only one disease. This systematic literature review reports the effect of pomegranate’s polyphenol in decreasing IL-6 level on macrophage and other pathologic cells by in vitro method focus at inflammatory disease that includes alzheimer’s, inflammatory bowel disease, cancer, metabolic disease and degenerative disease such as  rheumatoid arthritis, osteoarthritis, osteoporosis, and atherosclerosis.Method: Systematic literature review. Data were colected from Google Scholar and PubMed Central. The keywords used are “punica granatum,  inflammation, interleukin-6”. 19  papers which fullfilled the inclusion criteria reported the effect of pomegranate (Punicagranatum l.) to IL-6.Result: Active substance like punicalagin, ellagic acid, gallic acid, urolithin A/B, granatin A/B and delphinidin from the flower, seed, skin, mesocarp (inner skin) and all parts of pomegranate are reported to decrease the interleukin-6 (IL-6) level in diseases involving inflammation patophysiology, which include inflammatory disease such as inflamatory bowel disease and alzheimer’s, cancer, metabolic disease and degenerative disease include rheumatoid arthritis, osteoarthritis, osteoporosis, and atherosclerosis.Keyword: Punica granatum, Inflammation, Interleukin-6, In Vitro